Study of intragastric structuring ability of sodium alginate based o/w emulsions under in vitro physiological pre-absorptive digestion conditions - Soukoulis, Christos; Fisk, Ian D.; Bohn, Torsten; Hoffmann, Lucien (Elsevier, 2016)
In the present work, the intragastric structuring ability of o/w emulsions either stabilised (1–4%, w/w of sodium alginate (SA)) or structured with sheared ionic gel (1–3%, w/w of SA crosslinked with Ca2+) in the absence (saliva and gastric phases constituted of deionised water) or presence of in vitro pre-absorptive conditions (physiological simulated saliva and gastric fluids) was investigated. Visualisation of the morphological aspects of the gastric chymes, in the absence of multivalent counterions, demonstrated that SA stabilised systems underwent a remarkable swelling in the pH range of 2–3, whilst at the same pH range, ionic SA gel structured systems maintained their major structure configuration. When the aforementioned systems were exposed to physiological intragastric fluids, a reduction of the length and the hydrodynamic volume of the alginate fibres was detected regardless the structuring approach. On their exposure to physiological intragastric conditions (pH = 2), SA stabilised emulsions underwent sol–gel transition achieving a ca. 3- to 4-order increase of storage modulus (at 1 Hz). In the case of ionic sheared gel structured emulsions, exposure to physiological intragastric fluids resulted in a 10-fold reduction ability of their acid structuring ability, most likely due to the dialysis of egg-box dimer conformations by monovalent cations and protons and the sterical hindering of hydrogen bonding of MM and GG sequences under acidic conditions. Using of non-physiological simulated intragastric fluids was associated with overestimated structuring performance of SA regardless its physical state.